Performance of adjuvant treatment correlates with survival in reoperated glioblastomas - Zanovello, Willey Gonçalves; Malheiros, Suzana M. F.; Stavale, João Norberto; Lanzoni, Orestes P.; Canteras, Miguel M.; Santos, Adrialdo J.; Slaviero, Felipe; Fernandes, Bruno; Cavalheiro, Sergio; Paiva, Manoel A. de, Neto (Arquivos de Neuro-Psiquiatria, 2016)
Objective To analyze cases of recurrent glioblastoma subjected to reoperation at a Brazilian public healthcare service.Methods A total of 39 patients subjected to reoperation for recurrent glioblastoma at the Department of Neurosurgery, São Paulo Hospital, Federal University of São Paulo, from January 2000 to December 2013 were retrospectively analyzed.Results The median overall survival was 20 months (95% confidence interval – CI = 14.9–25.2), and the median survival after reoperation was 9.1 months (95%CI: 2.8–15.4). The performance of adjuvant treatment after the first operation was the single factor associated with overall survival on multivariate analysis (relative risk – RR = 0.3; 95%CI = 0.2–0.7); p = 0.005).Conclusion The length of survival of patients subjected to reoperation for glioblastoma at a Brazilian public healthcare service was similar to the length reported in the literature. Reoperation should be considered as a therapeutic option for selected patients.
Keywords: glioblastoma; reoperation; general surgery; survival